EVALUATING THE ROLE OF PROTON MAGNETIC RESONANCE SPECTROSCOPY IN CHARACTERIZATION OF INTRACRANIAL LESIONS - Aboelnor, Mahmoud I.; Elhawary, Mohamed E.; Mahmoud, Mohamed A.E.; Saad, Mohamed A.M. (Acta Scientiae et Intellectus, 2024)
The aim of this study is to evaluate the role of MR spectroscopy in characterization of intracranial lesions including differentiation of neoplastic from non-neoplastic lesions as well as grading of malignant lesions in clinical practice, based on clinician opinion, requesting MR spectroscopy evaluation, in whom the clinical situation could not have explained by the results of conventional imaging or their results were equivocal warranting further work up. The spectroscopy technique was done utilizing short intermediate and short TE sequences over the lesion, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of the results of MRI spectroscopy and separately for each of its parameters compared to the result.